2010
DOI: 10.1007/s11240-010-9791-8
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated genetic transformation of sesame (Sesamum indicum L.)

Abstract: Sesame (Sesamum indicum) is an important oil seed crop that has not yet been transformed genetically. We report herein for the first time successful recovery of fertile transgenic plants of sesame from cotyledon explants inoculated with Agrobacterium tumefaciens carrying a binary vector pCAMBIA2301 that contains a neomycin phosphotransferase gene (nptII) and a b-glucuronidase (GUS) gene (uidA) interrupted with an intron. Green shoots recovered from A. tumefaciens-infected explants on selection medium [Murashig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…It is used to indicate transient and stable transformations (Serres et al 1992), and to estimate the relative contribution and strength of promoter elements in the transcriptional activation. Most recently, GUS histochemical assay was utilized in the production of markerfree Petunia hybrida and tomato (Khan et al , 2011, and in the production of a more efficient Agrobacterium tumefaciens-mediated transformation protocol in melon (Ntui et al 2010), in Lilium (Azadi et al 2010), in Petunia hybrida (Thirukkumaran et al 2009), in pineapple (Gangopadhyay et al 2009), in Piper colubrinum (Mani and Manjula 2011), in sesame (Yadav et al 2010), in…”
Section: Discussionmentioning
confidence: 99%
“…It is used to indicate transient and stable transformations (Serres et al 1992), and to estimate the relative contribution and strength of promoter elements in the transcriptional activation. Most recently, GUS histochemical assay was utilized in the production of markerfree Petunia hybrida and tomato (Khan et al , 2011, and in the production of a more efficient Agrobacterium tumefaciens-mediated transformation protocol in melon (Ntui et al 2010), in Lilium (Azadi et al 2010), in Petunia hybrida (Thirukkumaran et al 2009), in pineapple (Gangopadhyay et al 2009), in Piper colubrinum (Mani and Manjula 2011), in sesame (Yadav et al 2010), in…”
Section: Discussionmentioning
confidence: 99%
“…In light of the recent findings, many genes controlling the TAG biosynthetic pathway were identified, though the detail of FAD3 gene is yet to reveal. From the past few years reports of sesame transformation (Yadav et al 2010;Al-Shafeay et al 2011;Chowdhury et al 2014) were well documented. Although, a detailed knowledge of the FA biosynthetic pathway involved in lipid synthesis for sesame is not documented, but FA profile suggested that, other related vegetable oil plant FA synthesis definitely carry the similarity with sesame.…”
Section: Fatty Acid Desaturase Gene(s) In Plants and Their Functionmentioning
confidence: 99%
“…Tissue culture and regeneration through in vitro culturing can speed up breeding process by producing a number of stable regenerants via callus or somatic embryogenesis in a short span of time. In sesame in vitro culturing, cotyledon (Yadav et al 2010 ) hypocotyl and shoot tips (Baskaran and Jayabalan 2006 ) have been reported to be more responsive to callus induction and plant regeneration. Appropriate concentrations of plant growth regulators and their combinations are very important to achieve successful plant regeneration from cultured cells and tissues, and were optimized in different studies.…”
Section: In Vitro Culture and Screeningmentioning
confidence: 99%
“…Appropriate concentrations of plant growth regulators and their combinations are very important to achieve successful plant regeneration from cultured cells and tissues, and were optimized in different studies. Application of BAP (benzylaminopurine) in the nutrient media was reported essential and the most effective cytokinin for shoot induction and plant regeneration in S. indicum (Yadav et al 2010 ) . Baskaran and Jayabalan ( 2006 ) studied the effects of plant growth regulators on callus induction in hypocotyls and cotyledon explants of sesame, and reported callus induction on media containing 2.2-22.6 m M 2, 4-D and 2.6-26.8-m M NAA ( a -naphthalene acetic acid), increased shoot proliferation on BAP and Kn (kinetin), whereas rooting took place on NAA (8.0 m M).…”
Section: In Vitro Culture and Screeningmentioning
confidence: 99%
See 1 more Smart Citation